2016
DOI: 10.21037/jtd.2016.02.20
|View full text |Cite
|
Sign up to set email alerts
|

Giant saccular superior vena cava aneurysm—a rare and difficult clinical case

Abstract: A superior vena cava (SVC) aneurysm is an extremely rare case of vascular malformation in the chest cavity. This is a report of a case of a 57-year-old woman with a saccular SVC aneurysm which was 8 cm wide. The chest computed tomography (CT) scan confirmed a giant 75 mm × 79 mm × 81 mm mass containing the contrast medium from SVC, constricting the right lung parenchyma, narrowing the right innominate vein, in contact with the anterolateral chest cavity wall, and adjoining the superior mediastinum.Under genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…It has been suggested that asymptomatic aneurysms with diameters < 40 mm can be managed conservatively with periodic scans and anticoagulation. (4) This is especially so for fusiform aneurysms that have lower complication rates. (5) Thrombolytic therapy with recombinant tissue plasminogen activator was deemed to be harmful in one case, in which mobilisation of the thrombus in the SVC aneurysm resulted in recurrent pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that asymptomatic aneurysms with diameters < 40 mm can be managed conservatively with periodic scans and anticoagulation. (4) This is especially so for fusiform aneurysms that have lower complication rates. (5) Thrombolytic therapy with recombinant tissue plasminogen activator was deemed to be harmful in one case, in which mobilisation of the thrombus in the SVC aneurysm resulted in recurrent pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Surgical resection, usually through a median sternotomy approach, has been advocated for saccular aneurysms due to risks of complications, (1) and for aneurysms that are larger than 40 mm, growing or symptomatic, or those that contain thrombi. (4) Cardiopulmonary bypass should be used when operating on saccular or complex aneurysms, such as those with venous obstruction, calcification or thrombus formation, to prevent pulmonary embolism. (4,6) Endovascular approaches can be considered for patients with high surgical risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism by which these aneurysms form has not been elucidated, but suggested theories include congenital abnormalities, inflammation, infection, mechanical trauma, and pathologic deficiencies of the SVC longitudinal muscle wall adventia. [3][4][5] An association with cystic hygromas has been suggested because of the similar embryologic origins of the venous and lymphatic systems. 3 Often, the exact etiology of SVC aneurysms cannot be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore subsequently started anticoagulant therapy in the present case. The treatment strategy for SVC aneurysms has not been established; however, a recent report suggested that asymptomatic aneurysms <40 mm in diameter might be best approached with conservative observation and anticoagulant therapy 4.…”
Section: Clinical Imagementioning
confidence: 99%